1996
DOI: 10.1136/bmj.313.7063.979
|View full text |Cite
|
Sign up to set email alerts
|

Is lead in tap water still a public health problem? An observational study in Glasgow

Abstract: Tap water lead and maternal blood led concentrations in the Loch Katrine water supply area have fallen substantially since the early 1980s. Maternal blood lead concentrations are well within limits currently considered safe for human health. Tap water lead is still a public health problem in relation to the lead exposure of bottle fed infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 20 publications
2
25
0
1
Order By: Relevance
“…These findings agree with other studies in the U.K. reported by Delves et al [25] and Watt et al [23]. No child in the present study had a blood lead 0.71 µmol\l ( 15.0 µg\dl).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These findings agree with other studies in the U.K. reported by Delves et al [25] and Watt et al [23]. No child in the present study had a blood lead 0.71 µmol\l ( 15.0 µg\dl).…”
Section: Discussionsupporting
confidence: 95%
“…These sources include old paint of high lead concentration, house dust or contaminated soil that may be ingested by young children, especially those with pica [22]. The water supply in certain areas may be above the recommended maximum lead concentration [17,23], while in communities adjacent to congested traffic conditions, the atmosphere may contain raised lead levels [24].…”
Section: Discussionmentioning
confidence: 98%
“…In Loch Katrine water supply area (Glasgow, UK) Watt et al (1996) found that 17% of the studied households with infants had lead concentrations of 10 mg/l or higher in kettle samples of their tap water compared to 49% in the year 1981. Tap water lead was the main correlate of raised maternal blood-lead concentrations and accounted for 62% and 76% of cases of maternal blood lead concentrations above 5 and 10 mg/dl, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Drinking water distributed through lead pipes can be an important source of lead exposure affecting blood lead concentrations in the general population (Meyer et al 1992;Krause et al 1996;Watt et al 1996;Fertmann et al 2004; Centers for Disease Control and Prevention [CDC] 2004). The contamination of drinking water by its contact with the distribution network and home plumbing is mainly caused by corrosion of metal parts.…”
Section: Introductionmentioning
confidence: 98%
“…Neben anderen Expositionswegen kann durch bleiha|tiges Rohrmaterial geleitetes Trinkwasser eine wichtige Ursache fiir erh6hte Blut-Bleiwerte in der Gesamtbev61kerung sein (Meyer et al 1992, Krause et al 1996, Watt et al 1996. Weitere wichtige Quellen k6nnen zum Beispiel bleihaltige Farben (Davies et al 1990, Lanphear und Roghmann 1997, Emissionen aus Industrie und Bergbau (Trepka et al 1997) und Blei im Hausstaub (Lanphear et al 1998) und Boden (Jin et al 1997) sein.…”
Section: Abstract Lead Contamination Of Drinking Water Caused By Theunclassified